The monoammoniate of lithium borohydride, Li(NH3)BH4: an effective ammonia storage compound. - Johnson, SR; David, W; Royse, D; Sommariva, M; Tang, C; Fabbiani, F; Jones, M; Edwards, P (2009)
Lithium borohydride absorbs anhydrous ammonia to form four stable ammoniates; Li(NH(3))(n)BH(4), mono-, di-, tri-, and tertraammoniate. This paper focuses on the monoammoniate, Li(NH(3))BH(4), which is readily formed on exposure of LiBH(4) to ammonia at room temperature and pressure. Ammonia loss from Li(NH(3))BH(4) commences around 40 degrees C and the compound transforms directly to LiBH(4). The crystal structure of Li(NH(3))BH(4) is reported here for the first time. Its close structural relationship with LiBH(4) provides a clear insight into the facile nature and mechanism of ammonia uptake and loss. These materials not only represent an excellent high weight-percent ammonia system but are also potentially important hydrogen stores.